PENINGKATAN AKTIVITAS DAN HASIL BELAJARKETERAMPILAN MENULIS MATERI DESCRIPTIVE TEXTMELALUI MODEL PEMBELAJARAN MAKE A MATCH DENGAN MEDIA GAMBAR SERI PADA SISWA KELAS VII I SMP NEGERI 1 PANGKAH SEMESTER GENAP TAHUN PELAJARAN 2018/2019 - dan Yoga Prihatin, Hery Krisnanto, Tity Kusrina, (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2021)
This study aims to: 1) determine whether the application of the Make a Match learning model with Series Image Media can increase the activity and learning outcomes of writing skills in Descriptive Text material in grade VII I SMP Negeri 1 Pangkah Semester Even in the 2018/2019 Academic Year; 2) knowing how the process of implementing the Make a Match learning model with Media Image Series takes place as an effort to improve writing skills of Descriptive Text material for grade VII I students of SMP Negeri 1 Pangkah Even Semester 2018/2019 Academic Year. This research was conducted in 2 cycles, and based on the analysis of the results of the observations and assessments conducted by the researcher, it can be concluded that: 1) the results of the study in the initial conditions showed a lack of enthusiasm for student learning 2) the activities and learning outcomes of students on writing skills of descriptive text material in Cycle I and Cycle II which is obtained has increased.